Previously Unidentified Turkish Words in the Syrian Dialect of Arabic - Muhammed Akif (Şarkiyat Mecmuası)
Language is a living organism that both influences and is influenced by others, and interaction between languages is a natural process. Due to geographical and cultural proximity, Turkish and Arabic languages, along with their dialects, have experienced such interactions. The Syrian dialect is among those Arabic dialects heavily influenced by Turkish. Numerous Turkish words have been integrated into the Syrian dialect and are still used today. These words have even led to the creation of new verbs not found in Turkish. However, past studies on Arabic dialects and Turkish-derived words have either not identified or overlooked the Turkish origins of many such words. This study focuses on identifying Turkish words in the Syrian dialect whose origins remain unknown or unmentioned. Approximately 65 words were found, some clearly of Turkish origin, but previously undocumented or unproven. A historical-descriptive approach was used to trace these words, verify their Turkish origins, and resolve doubts about their etymology. Additionally, the meanings and usage of these words in the Syrian dialect were clarified with examples from daily language. This study highlights the overlooked Turkish roots of many words in Arabic dialects, emphasizing an important dimension of Turkish-Arabic language interaction.